2016
DOI: 10.18632/oncotarget.11133
|View full text |Cite
|
Sign up to set email alerts
|

The role of nerve microenvironment for neurofibroma development

Abstract: Deregulation of RAS signaling in Neurofibromatosis type 1 (NF1) results in the development of multiple neurofibromas, complex tumor of the peripheral nerves with no effective medical treatment. There is increasing evidences that neurofibroma initiates through loss of NF1 function in the Schwann cell lineage, followed by a cascade of interactions with other cell types in the surrounding tumor microenvironment. In NF1 patients, neurofibromas always develop along peripheral nerves and do not migrate to distant or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“… 23 25 Studies in mouse models have identified a critical role for mast cells in pNF formation, but it is unknown whether mast cells and macrophages contribute to the growth of cNF tumours. 23 , 24 , 26 Histologically, cNFs share similar markers to other NF1-associated nerve tumours such as pNFs, and can be identified by wavy nuclei, S100 positivity and the expression of collagen IV, Sox10, CD34 and CD44. Of note, S100 and Sox10 can be used as diagnostic markers.…”
Section: Histology Origin and Pathogenesis Of Cnfmentioning
confidence: 99%
See 2 more Smart Citations
“… 23 25 Studies in mouse models have identified a critical role for mast cells in pNF formation, but it is unknown whether mast cells and macrophages contribute to the growth of cNF tumours. 23 , 24 , 26 Histologically, cNFs share similar markers to other NF1-associated nerve tumours such as pNFs, and can be identified by wavy nuclei, S100 positivity and the expression of collagen IV, Sox10, CD34 and CD44. Of note, S100 and Sox10 can be used as diagnostic markers.…”
Section: Histology Origin and Pathogenesis Of Cnfmentioning
confidence: 99%
“…More recent work demonstrated that implantation of Nf1 −/− SKPs in sciatic nerve tissue, but not subcutaneous implantation in unprimed athymic mice, resulted in neurofibroma formation, further indicating that the microenvironment may be a key regulator of cNF development. 24 …”
Section: Histology Origin and Pathogenesis Of Cnfmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, there was no correlation between the incidence of recurrence∖malignant degeneration and the clinical∖histological type of neurofibroma in our cohort. These observations might tentatively be linked to peculiar aspects of the maturation and differentiation of Schwann cells in neurofibromas, which might translate into different concentrations of the cytoplasmatic content of neurofibromin, arising from differences in the morphological expression of genetic alterations of the NF1 gene (monoallelic or biallelic) [ 2 6 ] and the neural microenvironment [ 7 ]. Of course this is just speculation at present, and further immunohistochemical studies will need to demonstrate the possible link between neurofibromin content, fluorescence, and neurofibroma behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral nerve diseases [ 1 11 ] commonly seen in the clinic include peripheral nerve sheath tumors [ 12 15 ], optic nerve injury [ 16 , 17 ], peripheral nerve chronic constriction injury [ 18 ], and peripheral nerve defects. Clinical [ 19 , 20 ] and experimental [ 21 23 ] research has been carried out to find ways to treat peripheral nerve diseases. Absence of suitable nerve replacement grafts is the main hurdle to improving the low repair rate of peripheral nerve defects.…”
Section: Introductionmentioning
confidence: 99%